Is the Short Follicular Phase in Older Women Secondary to Advanced or Accelerated Dominant Follicle Development? - Klein, Nancy A.; Harper, Andrew J.; Houmard, Brenda S.; Sluss, Patrick M.; Soules, Michael R. (The journal of clinical endocrinology and metabolism, 2002)
This study sought to determine whether the shortened follicular phase in ovulatory older women is secondary to advanced (i.e. earlier) or accelerated (i.e. more rapid) folliculogenesis. Normal ovulatory women, aged 40–45 yr (n = 15) and 20–25 yr (n = 13), underwent daily venipuncture and transvaginal ultrasonography throughout the follicular phase of a spontaneous menstrual cycle (control cycle) and after pituitary down-regulation with a GnRH agonist (study cycle). As expected, the older subjects in the control cycles demonstrated an elevated d 3 FSH and a shortened follicular phase compared with the younger subjects. After release from hypothalamic-pituitary-ovarian axis suppression, the early follicular phase FSH peak occurred earlier (6.8 vs. 9.8 d; P < 0.01) and was of a greater magnitude (12.1 vs. 6.5 mIU/ml; P < 0.01) in the older subjects. The time from release of suppression until the subsequent LH surge was also shorter (17.5 vs. 20.8 d; P < 0.01) in the older group. However, the time from FSH peak to LH surge was similar in the older and younger groups (10.7 vs. 11.0 d; P = 0.74). Compared with younger women, older subjects had normal follicular phase levels of estradiol and inhibin A and lower levels of inhibin B in both control and study cycles. We conclude that the shortened follicular phase observed in older ovulatory women is due to earlier dominant follicle selection, independent of hormonal influences from the preceding luteal phase.